Predictors of severe disease in a hospitalized population of children with acute viral lower respiratory tract infections (2015)
Although predictors of severe viral acute lower respiratory infections (ALRIs) in children have been reported, there have been few research studies performed in low‐ and middle‐income countries (LMIC). The aim of the present study was to determine predictors of disease severity in a population of Colombian children <5 years of age with ALRI. In a prospective cohort study, we determined independent predictors of severe ALRI in a hospitalized population of children under 5 years old with ALRI during a 1‐year period. We included both underlying disease conditions and the infecting respiratory viruses as predictor variables of severe disease. We defined severe disease as the necessity of pediatric intensive care unit admission. Of a total of 1,180 patients admitted with a diagnosis of ALRI, 416 (35.3%) were included because they were positive for any kind of respiratory virus. After controlling for potential confounders, it was found that a history of pulmonary hypertension (RR 3.62; CI 95% 2.38–5.52; P  < 0.001) and a history of recurrent wheezing (RR 1.77; CI 95% 1.12–2.79; P  = 0.015) were independent predictors of severe disease. The present study shows that respiratory viruses are significant causes of ALRI in infants and young children in Colombia, a typical tropical LMIC, especially during the rainy season. Additionally, the results of the present study show that clinical variables such as a history of pulmonary hypertension and a history of recurrent wheezing are more relevant for predicting ALRI severity than the infecting respiratory viruses.